ANALYSIS OF THE INFLUENCE OF FUNDAMENTAL FACTORS ON FIRM VALUE IN TELECOMMUNICATIONS COMPANIES LISTED ON THE BEI - Juliani Khairul, Nila; Widhi Kurniawan, Agung; Nurman; Tawe, Amiruddin; Aslam, Annisa Paramaswary (Journal Management & Economics Review (JUMPER), 2023)
This study aims to determine the effect of liquidity, solvency, and profitability on firm value. The independent variables in this study are liquidity, solvency, and profitability. The dependent variable in this study is firm value. The population in this study is telecommunications companies listed on the IDX for the period 2015-2022. The method of determining the sample that was used in this study was purposive sampling, namely the sampling technique using certain criteria, obtained 5 companies that met the sample criteria in this study so that the total sample in this company was 40 samples. The analysis method used in this study is multiple linear regression analysis method. The results of this study indicate that liquidity has a negative but insignificant effect on firm value while solvency and profitability have a positive and significant effect on firm value.